Architecture of a new infrastructure for data service in DT era - Gengsheng HUANG; Yuhong HUANG; Manxue GUO; Jianping ZHENG; Xin GE (Dianxin kexue)
Data technology (DT) era centered on the data technology and data service was coming.To handle the major challenges in the data exchange and transactions, a new infrastructure - data sharing service network (DSSN) was proposed, which provided the data interconnection, exchange, transactions, supervision and other services for regulators, data providers, data applications and technical support providers.The design principles of DSSN system were outlined as compliance, security, fairness, openness and connection service.And the architecture of DSSN system was designed according to the principles.A layered architecture was applied to the data sharing service node with the service control layer and service capability layer.The data node was composed of the data sharing dedicated server and data source, and was connected to DSSN through data gateway.